The Effectiveness of The Group Investigation Model with a Jelajah Alam Sekitar Approach to The Metacognitive Skills of High School Students in Animalia Material - Budiman, Wahyu Nur; Marianti, Aditya (FMIPA UNNES, 2020)
This study aims to analyze the group investigation model's effectiveness with a Jelajah Alam Sekitar (JAS) approach to the metacognitive skills of high school students. This research was conducted at SMA N 1 Bumiayu in the even semester of the 2019/2020 school year. The research design was a Pre-experimental type of One-Group Pre-test-Post-test Design. All students of Class X MIPA SMA N 1 Bumiayu as the population of this research. This research sample was the students of Class X MIPA 1 and 2 taken by a purposive random sampling technique. The results showed that the metacognitive skills of students averaged a score of 75.19, which was in the good criteria. Journal analysis of student learning activities shows that 81.94% has medium criteria. Metacognitive ability test results have an average score of 73.13 in the good criteria. Students' cognitive ability to achieve classical completeness is 79.19%, and the level of students' understanding of the material based on the results of the N-gain test is at the medium criteria. The correlation between metacognitive abilities using a questionnaire with cognitive abilities showed no significant relationship with a large correlation coefficient of 0.018 (very low). On the other side, the correlation of metacognitive skills using tests with cognitive abilities showed a significant relationship with a large correlation coefficient of 0.495 (medium). Students and teachers gave positive responses to the group investigation learning model with a natural exploration approach. The conclusion of this research is the application of a group investigation learning model with a JAS around effectively the metacognitive skills of high school students on Animalia material.